REEVALUATING TEACHING STRATEGIES IN MATHEMATICS AND STATISTICS !N SECONDARY SCHOOLS - Mohd Sahar Sauian (Proceedings of ICMSA, 2005)
Numerous studies had shown that rural students are lagged behind inmathematical subjects compared to their urban counterparts,particularly in developing countries. This argument is normallycharacterized and expounded by exposing the negative factors such asstudents' attitude, cultural background, poor environment andfacilities, command of language, lack of graduate teachers as well aspoor mode of teaching methodologies. It has also been known thatthe single factor of